Monitoring of Natural Enemies (Hymenoptera) on Different Lands Use: Study from Agroforestry, Community Forest, and Pioneer Land - Ananto Triyogo; Akbar Zhafran Adriansyah; Dwi Tyaningsih Adriyanti (Institut Pertanian Bogor (IPB University), 2022)
Land use and management must be carried out in a way that ensures the sustainability of land ecological function. The presence of natural enemies that suppress pest populations is an important component of the ecological function. Monitoring the presence of natural enemies and avoiding silvicultural activities that threaten the presence of natural enemies are important aspects of land management. This study investigates the presence of natural enemies on three different lands: agroforestry, community forests, and pioneer lands. Monitoring was carried out during three months at three types of land use by using observation plot in the square form of 20 x 20 m2. Insect collection in the field uses pitfalls and sticky traps which are placed using a grid and a diagonal method, respectively. Phytophagous insects, such as leafhopper, flies, thrips, aphids were surveyed. Hymenoptera natural enemies, predators (Formicidae) and parasitic wasps (Trichogrammatidae and Scelionidae) were obtained. The results show that community forests and pioneer lands are support the existence of Formicidae. This study indicates that in the agroforestry there are variations in population of Formicidae based on the period of on-going land management. Agroforestry provides a more suitable place for the existence of Trichogrammatidae and Scelionidae.